(3GdLGeY dUaGJ CTJGJ GdfHGJs - (3GdEOQjSj , eMeO Hf eMeO Hf YHO Gddg Hf EOQjS GdMSfj GdWGdHj, CHh YHO Gddg,J (B560 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GdMeO ddg GdPj CMGW Hcd TF YdekG hHYO aEf CfGSkG ef Cgd ReGffG jOYhf eGdGYde dge Hg hjfSHhf Edi eYQaI GdMTGFT hGdGTLGQ hGdeYGOf hGdMjhGfGJ s
(3BNQgG (B:s
(3ef BNQ GdehLhO Hg hdh cGfJ aj ChGFd GdYVd hEPG JVeO HhQbI edd GdGhQGe GdQNhI hjbGhe LejY GdLQGMGJ aj Chd GHJOGFgG hjeRb GdLQGMGJ HOegG s
(3QJHI Ydi MQha GdeYLes
(3hGdajde eXde CcKQg hJhLO fSNI CNQj Yf LGeYI jhJG (B- (3HQbe (B185 (3WHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B24 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B236s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3eJaQbGJs